Perception Of Saudi Arabia Residents’ Towards Tourism Development In Saudi Arabia - Abdulqader, Al-Sakkaf Mohammed Alawi (2023)
Tourism is recognized as a tool for community development in developing countries, particularly in Saudi Arabia. It is frequently viewed as an instrument for economic diversification, facilitating the improvement of quality of life and protecting natural and cultural resources. However, studies show that tourism development has both positive and negative effects on residents’ quality of life in various ways, including economic, sociocultural, and environmental factors. As a result, tourism planners and stakeholders must understand residents' perceptions of tourism development and its effects during the planning stage of tourism development. The study examines how residents in Saudi Arabia perceive the economic, sociocultural, and environmental impacts of tourism, as well as how this affects their quality of life and support for tourism development, with quality of life as a mediator and destination social responsibility as a moderator. This study used a quantitative method, including a survey using questionnaires.